Suicidal behavior in individuals with substance use disorder who apply to the probation outpatient clinic - Uğur, Kerim; Tamam, Lut; Demirkol, Mehmet Emin; Yıldız, Sevler; Kartal, Fatma; Kazğan, Aslı; Polat, Hatice (Journal of Dependence, 2021)
Objective: The aim of this study was to investigate the correlation between psychological pain, childhood mental trauma, alexithymia, impulsivity and psychological resilience and suicide attempts in individuals with substance use disorder (SUD) who applied to the Probation Outpatient Clinic.Method: The study was conducted with 120 individuals who applied to the probation outpatient clinic and healthy controls. Socio-Demographic Data Form, Childhood Psychological Trauma Scale (CTQ-28), Toronto Alexithymia Scale (TAS), Psychological Pain Scale (PP), Barratt Impulsiveness Scale (BIS), Psychological Resilience Scale (PRS) were applied to all participants.Results: PP, TAS, BIS, CTQ-28 scale scores of patients with suicide attempt history were higher. In the forward stepwise model designed to predict the risk of suicide attempt, PRS, TAS-A, PRS-social competence and BIS-total scores contributed significantly to the model. It was determined that the four significant variables explained 65,6% of the variance in suicide risk.Conclusion: High psychological pain, alexithymia, impulsivity and childhood trauma and low psychological resilience in individuals with substance use disorder could be a predictor of suicide risk.
Keywords: Probation; substance use disorder; childhood traumas; alexithymia